Altered SOX9 genital tubercle enhancer region in hypospadias. Issue 170 (June 2017) - Sreenivasan, Rajini; Gordon, Christopher T.; Benko, Sabina; de Iongh, Robb; Bagheri-Fam, Stefan; Lyonnet, Stanislas; Harley, Vincent
Highlights: Alterations in a genomic region upstream of SOX9 cause disorders of sex development. A putative enhancer within this region, SR4, is active in the genital tubercle. A novel domain of SOX9 protein expression was discovered in the genital tubercle. SR4 may function as a Sox9 genital tubercle enhancer. SR4 and SOX9 mutations may lead to hypospadias (misplaced urethral opening). Abstract: Human mutations in the SOX9 gene or its regulatory region can disrupt testicular development, leading to disorders of sex development (DSDs). Our previous work involving the genomic analysis of isolated DSD patients revealed a 78 kb minimal sex determining region (RevSex) far upstream of SOX9 that was duplicated in 46, XX and deleted in 46, XY DSDs. It was postulated that RevSex contains a gonadal enhancer. However, the most highly conserved sub-region within RevSex, called SR4, was neither responsive to sex determining factors in vitro nor active in the gonads of transgenic mice, suggesting that SR4 may not be functioning as a testicular enhancer. Interestingly, SR4 transgenic mice showed reporter activity in the genital tubercle, the primordium of the penis and clitoris, a previously unreported domain of Sox9 expression. SOX9 protein was detected in the genital tubercle, notably in the urethral plate epithelium, preputial glands, ventral surface ectoderm and corpus cavernosa. SR4 may therefore function as a Sox9 genital tubercle enhancer, mutations of which could possibly lead to hypospadias, a birth defect seen in the DSD patients in the RevSex study. SR4 activity and the observed SOX9 expression pattern suggest that SR4 may function as a Sox9 genital tubercle enhancer. However, conditional ablation of Sox9 in the genital tubercle using Shh-Cre/+;Sox9 flox/flox mice revealed no genital tubercle abnormalities, possibly due to compensation by similar Sox factors. To conclude, we have identified a novel regulatory enhancer driving Sox9 expression during external genitalia development.